2004
DOI: 10.1074/jbc.m407810200
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Growth Factor (CTGF) Is Regulated by Wnt and Bone Morphogenetic Proteins Signaling in Osteoblast Differentiation of Mesenchymal Stem Cells

Abstract: Osteoblast lineage-specific differentiation of mesenchymal stem cells is a well regulated but poorly understood process. Both bone morphogenetic proteins (BMPs) and Wnt signaling are implicated in regulating osteoblast differentiation and bone formation. Here we analyzed the expression profiles of mesenchymal stem cells stimulated with Wnt3A and osteogenic BMPs, and we identified connective tissue growth factor (CTGF) as a potential target of Wnt and BMP signaling. We confirmed the microarray results, and we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
356
4
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 295 publications
(371 citation statements)
references
References 73 publications
(107 reference statements)
8
356
4
3
Order By: Relevance
“…It is not unusual for intracellular and extracellular proteins to be necessary for a biological effect, but when expressed in excess to be inhibitory. For example, Hes-1 is necessary for adipogenesis, but its overexpression inhibits adipogenesis, twisted gastrulation and connective tissue growth factor are necessary for BMP effects on osteoblastogenesis, but when in excess they can be inhibitory [48][49][50][51]. Similarly, CHOP is necessary for normal osteoblastic function, but when in excess, and under specific conditions in vivo, it may interact with intracellular proteins necessary for osteoblastic function and become inhibitory.…”
Section: Discussionmentioning
confidence: 99%
“…It is not unusual for intracellular and extracellular proteins to be necessary for a biological effect, but when expressed in excess to be inhibitory. For example, Hes-1 is necessary for adipogenesis, but its overexpression inhibits adipogenesis, twisted gastrulation and connective tissue growth factor are necessary for BMP effects on osteoblastogenesis, but when in excess they can be inhibitory [48][49][50][51]. Similarly, CHOP is necessary for normal osteoblastic function, but when in excess, and under specific conditions in vivo, it may interact with intracellular proteins necessary for osteoblastic function and become inhibitory.…”
Section: Discussionmentioning
confidence: 99%
“…29 We previously demonstrated that CTGF is upregulated at the early stage of osteogenic differentiation. 29 We analyzed the basal CTGF expression in human OS cells.…”
Section: Connective Tissue Growth Factor Is Highly Expressed In Uncommentioning
confidence: 99%
“…29 We previously demonstrated that CTGF is upregulated at the early stage of osteogenic differentiation. 29 We analyzed the basal CTGF expression in human OS cells. As shown in Figure 2c, almost all of the tested primary OS lines exhibited higher expression levels of CTGF than that of hFOB1.19, whereas MG63 (and to a lesser extent, U2OS) also had high basal level of CTGF expression.…”
Section: Connective Tissue Growth Factor Is Highly Expressed In Uncommentioning
confidence: 99%
See 1 more Smart Citation
“…The key step is the generation of recombinants in AdEasier cells. Once these recombinants are obtained, generation of adenoviruses in HEK-293 cells is virtually guaranteed [23][24][25][26][27] . Depending on the transfection efficiency of HEK-293 cells, one can expect titers in the initial lysate to be 10 8 -10 10 pfu ml À1 .…”
Section: Anticipated Resultsmentioning
confidence: 99%